The impact of horizontal mergers on rivals: Gains to being left outside a merger - Joseph Clougherty; Tomaso Duso (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2008)
It is commonly perceived that firms do not want to be outsiders to a merger between competitor firms. We instead argue that it is beneficial to be a non-merging rival firm to a large horizontal merger. Using a sample of mergers with expert-identification of relevant rivals and the event-study methodology, we find rivals generally experience positive abnormal returns at the merger announcement date. Further, we find that the stock reaction of rivals to merger events is not sensitive to merger waves; hence, 'future acquisition probability' does not drive the positive abnormal returns of rivals. We then build a conceptual framework that encompasses the impact of merger events on both merging and rival firms in order to provide a schematic to elicit more information on merger type.
urn:nbn:de:bvb:19-epub-13313-8
Keywords: G14; G34; L22; M20; 330; rivals; mergers; acquisitions; event-study